PENGALAMAN WISATAWAN DALAM STORYTELLING WISATA HOROR BANDROS BRAGA MYSTERY - Rahmawati, Dini; Retnasary, Maya; Fhaturahim, Iqbal (Universitas Pendidikan Ganesha, 2025)
Bandros Braga Mystery is a ghost tour conducted on Thursday night. The tour walks along an abandoned old building with dark history. This research aimed to analyse tourist experience storytelling as the main component. This is a qualitative research using observation, interview and documentation as well as literature study. Observation was conducted by becoming the tourists. Interview used semi-structured technique and purposive sampling as the base of selecting informants. Documentation was conducted by taking pictures and literature study was conducted by reading related articles and websites references of this article. The result showed that storytelling can make tourists imagine past events in the location. Tourists are emotionally connected to the story by feeling sad and terrified during the storytelling. Story about ghosts provides creepy feeling, although sometimes it is not well organized. Scary and tense are felt, supported by dark and cold as well as the remains and relics.